Procedure in respect of abdominal traumatism - Guicheff, Vladimir; Negrotto, Gonzalo (Cirugía del Uruguay, 1984)
Our procedures In respect of abdominal traumatlsm has changad In the last three years. By availlng added accuracy to the diagnosis, the laparoscopy technlque permlts to operate upon of patlents In whlch we dld not suspect splanchnlc lesion as well as to abstaln from an lnterventlon in cases not justlfylng lt on account of exlsting leslons. We draw percentages In respect of 160 flbrolaparoscoples performed in traumatizad pa• tlents, out of a total of 280 carrled out In cases of acute abdominal distress.